Competitive golf: How longer courses are changing athletes and their approach to the game - Zoffer, M. (Nutrients, 2022)
Nutritional guidance for competitive golfers to improve performance is limited. Recommendations and study conclusions from older research used smaller golf courses compared to today and require a reevaluation of energy expenditure. This review identifies aerobic fitness, in addition to strength, as a key determinant of success. A novel nutritional approach that incorporates carbohydrate supplementation to support aerobic fitness without sacrificing the ability to build strength is presented since longer courses require more stamina. Strategies for training, competition, and recovery are outlined based on different skill levels. American College of Sports Medicine (ACSM) guidelines for carbohydrates, protein, and hydration intake are tailored specifically for competitive golf based on this approach. Putting requires precise movement and can be affected by fatigue. Nutritional studies in golf and similar sports that require focused movements are presented, exhibiting an improvement with adequate hydration and carbohydrate status and caffeine use. Competitive golf poses unique challenges to an athlete and commonly used ergogenic supplements that can improve performance in a variety of circumstances during training, competition, and while traveling are reviewed.